Proceedings of the 2021 Conference on Empirical Methods in Natural Language Processing: System Demonstrations 2021
DOI: 10.18653/v1/2021.emnlp-demo.11
|View full text |Cite
|
Sign up to set email alerts
|

Thermostat: A Large Collection of NLP Model Explanations and Analysis Tools

Abstract: In the language domain, as in other domains, neural explainability takes an ever more important role, with feature attribution methods on the forefront. Many such methods require considerable computational resources and expert knowledge about implementation details and parameter choices. To facilitate research, we present THERMOSTAT which consists of a large collection of model explanations and accompanying analysis tools. THER-MOSTAT allows easy access to over 200k explanations for the decisions of prominent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Through our experiments, we discover (i) a general lack of correlation between explanation methods, especially for more complex settings (i.e., transformer-based model and pair-sequence tasks) which is corroborated by additional recent research on text, tabular, and image data [36,37], (ii) that similar explanations do not always result in correlated rankings, and (iii) the existence of a single "ideal" explanation is questionable, which is a fundamental assumption of the agreement as evaluation paradigm. Without an external ground-truth explanation, all that rank correlation tells us is whether or not two rankings are similar.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Through our experiments, we discover (i) a general lack of correlation between explanation methods, especially for more complex settings (i.e., transformer-based model and pair-sequence tasks) which is corroborated by additional recent research on text, tabular, and image data [36,37], (ii) that similar explanations do not always result in correlated rankings, and (iii) the existence of a single "ideal" explanation is questionable, which is a fundamental assumption of the agreement as evaluation paradigm. Without an external ground-truth explanation, all that rank correlation tells us is whether or not two rankings are similar.…”
Section: Discussionsupporting
confidence: 69%
“…In Section 5, we have shown that there is a low degree of correlation between explanation methods, especially for the transformer-based model. Similar conclusions are observed in the work of [36] and [37]. This makes it challenging to justify the expectation that in order for attention-based explanations to be valid, they should correlate with existing feature attribution methods.…”
Section: Lack Of Correlation Between Explanation Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…In Section 5, we have shown that there is a low degree of correlation between explanation methods, especially for the transformer-based model. 10 Similar conclusions are observed in the work of [36] and [37]. This makes it challenging to justify the expectation that in order for attention-based explanations to be valid, they should correlate with existing feature attribution methods.…”
Section: Lack Of Correlation Between Explanation Methodsmentioning
confidence: 63%
“…Currently, ferret includes three classificationoriented datasets annotated with human rationales, i.e., annotations highlighting the most relevant words, phrases, or sentences a human annotator attributed to a given class label (DeYoung et al, 2020;Wiegreffe and Marasovic, 2021). Moreover, ferret API gives access to the Thermostat collection (Feldhus et al, 2021), a wide set of pre-computed feature attribution scores.…”
Section: Dataset Apimentioning
confidence: 99%